1992
DOI: 10.2337/diab.41.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of The Insulin-Resistance Syndrome (Syndrome X)

Abstract: Many studies have shown that hyperinsulinemia and/or insulin resistance are related to various metabolic and physiological disorders including hypertension, dyslipidemia, and non-insulin-dependent diabetes mellitus. This syndrome has been termed Syndrome X. An important limitation of previous studies has been that they all have been cross sectional, and thus the presence of insulin resistance could be a consequence of the underlying metabolic disorders rather than its cause. We examined the relationship of fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
462
1
19

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,040 publications
(499 citation statements)
references
References 42 publications
17
462
1
19
Order By: Relevance
“…[1][2][3] Modan et al 4 suggested that there is a relationship between insulin levels and blood pressure, and several groups have hypothesized that insulin resistance and/or hyperinsulinemia contribute to the pathogenesis of hypertension. 5,6 Thus, insulin has an important role in pathophysiological regulation of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Modan et al 4 suggested that there is a relationship between insulin levels and blood pressure, and several groups have hypothesized that insulin resistance and/or hyperinsulinemia contribute to the pathogenesis of hypertension. 5,6 Thus, insulin has an important role in pathophysiological regulation of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Christlieb et al 5 found a causal relationship between the level of circulating insulin and diastolic BP at the first-year follow-up of subjects with impaired glucose tolerance. Haffner et al 11 observed an independent association in subjects with normal body weight and normoglycaemia. A causal relationship between the elevated fasting insulin concentration and the development of hypertension was found in this study.…”
Section: Discussionmentioning
confidence: 96%
“…One prospective study revealed that after adjustment for overweight and body fat distribution, fasting insulin was an independent risk factor for hypertension only in subjects with normal body weight and normoglycaemia, 11 whereas another study showed that changes in blood pressure (BP) preceded abnormal glucose tolerance, but not hyperinsulinaemia. 4 A study made on non-obese young adult black men with the euglycaemic hyperinsulinaemic clamp technique suggested that insulin resistance might precede the onset of established essential hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…10 More recently, an index incorporating fasting insulin and triglyceride levels, the McAuley index, has also been shown to be a sensitive marker of IR 11 and has attracted increasing use in clinical research. The presence of the metabolic syndrome (MetS) itself is also often used as a surrogate marker of IR, 12 with its characteristic abnormalities of a raised triglyceride (trig) to highdensity lipoprotein (HDL)-cholesterol ratio (trig:HDL) 13 and low circulating levels of the insulin-sensitizing adipocytokine, adiponectin, [14][15][16] shown to correlate with the degree of IR.…”
Section: Introductionmentioning
confidence: 99%